Contents of Fatty Acids, Selected Lipids and Physicochemical Properties of Western Australian Sandalwood Seed Oil - Hettiarachchi, Dhanushka; Liu, Yandi; Boddy, Michael; Fox, John; Sunderland, Vivian (Springer, 2013)
The study was designed to characterise two extracts of Western Australian sandalwood (Santalum spicatum) seed oils for their physicochemical and lipid characteristics. Sandalwood plantation’s surplus seeds could be used for their oil content, to improve the commercial viability of this industry. The seed oils were obtained by solvent extraction and supercritical carbon dioxide extraction respectively. Important physicochemical parameters were compared with other oils commonly used in pharmaceutical and cosmetic products. Acid values were found to be higher (6.0–7.5 mg KOH/1 g oil) while peroxide values (6.7–9.0 mequiv/Kg) were lower than reported for other oils. Tocopherols were found to be lower than those usually reported for nut oils (α-tocopherol 1–3 mg/100 g; δ-tocopherol 2.2–5.7 mg/100 g), squalenes and phytosterols were found in considerable quantities. The fatty acid content consisted largely of ximenynic acid (35 %) and oleic acid (52 %). No oxidative derivatives of fatty acids were observed. Although there were statistically significant differences in some properties, the magnitude of these were insufficient to conclude there were any notable differences in the two oil extracts.